2003
DOI: 10.1002/acp.939
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of eyewitness identification that predict the outcome of real lineups

Abstract: Data were analysed from 640 attempts by eyewitnesses to identify the alleged culprit in 314 lineups organized by the Metropolitan Police in London. Characteristics of the witness, the suspect, the witness's opportunity to view the culprit, the crime and the lineup were recorded. Data analysis, using mixed effects multinomial logistic regression, revealed that the suspect was more likely to be identified if the witness is younger than 30, the suspect is a white European (rather than AfricanCaribbean), the witne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 37 publications
4
119
2
Order By: Relevance
“…An archival study of criminal cases in the USA found that identification of the police suspect was more likely if the lineup occurred within 7 days (55%) rather than after 7 days (45%; Behrman & Davey, 2001). Similarly, Valentine et al (2003) found that 65% of witnesses identified the police suspect from live lineups held within 7 days but only 40% identified the suspect if the lineup was held more than 7 days after the incident. In archival studies it cannot be established independently how many suspects are the culprit.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An archival study of criminal cases in the USA found that identification of the police suspect was more likely if the lineup occurred within 7 days (55%) rather than after 7 days (45%; Behrman & Davey, 2001). Similarly, Valentine et al (2003) found that 65% of witnesses identified the police suspect from live lineups held within 7 days but only 40% identified the suspect if the lineup was held more than 7 days after the incident. In archival studies it cannot be established independently how many suspects are the culprit.…”
Section: Methodsmentioning
confidence: 99%
“…Pezdek and Blandon-Gitlin (2005) found no effect of commitment from a first lineup, which followed 2 hours after viewing a target face, on identification from a second lineup after 1 month. The effect of delay found in archival studies of police lineups suggests that a delay of more than 7 days may have a significant impact on identification ability (e.g., Valentine et al 2003). Therefore, the aim of Experiment 3 was to examine the effect of delay after taking part in a live showup on the outcomes of a video lineup held 1 -6 days, or 9 -30 days later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the results of field studies raise the possibility that variables (such as memory strength) within the eyewitness context might moderate the effects of primary eyewitness variables. For instance, field studies examining the weapon focus effect did not find significant differences in suspect identification rates depending on whether a weapon was present (Behrman & Davey, 2001;Valentine, Pickering, & Darling, 2003;Wright & McDaid, 1996), or depending on whether the witness was subjected to violence (Wright & McDaid, 1996). Additionally, field studies have found mixed results regarding the cross-race effect (Behrman & Davey, 2001;Valentine, Pickering, & Darling, 2003).…”
mentioning
confidence: 97%
“…In contrast to Levi's studies, however, the learning was not incidental, which explains the higher identification rate. The identification rate is an important issue if we expect police to adopt a large lineup, and a 30% rate may satisfy police departments (see Valentine, Pickering & Darling, 2003 for an extensive summary of real lineup data predating the English video lineup).…”
Section: Recruitment and Eyewitness Conditionmentioning
confidence: 99%